Amiodarone - a new type of antiarrhythmic drug. Issue 22 (23rd October 1981) - Unknown
Abstract : Amiodarone (Cordarone X - Labaz) is an antiarrhythmic drug which has been available in some European and South American countries for several years. In Britain the product licence is restricted to the treatment of tachycardias associated with Wolff-Parkinson-White (WPW) syndrome (intermittent arrhythmias mediated by an accessory pathway between atria and ventricles), and paroxysmal tachycardias when other drugs cannot be used.